Inkaber as an Innovation Learning Model to Improve Reading and Writing Skills for Beginners - Alfajriya, Anita; Taufiq, Ahmad (Tadibia Islamika: Journal of Holistic Islamic Education, 2021)
The objective of this study is to assess students' reading and writing skills using the Inkaber model at MI Islamiyah Reban. It delves into the planning of the Inkaber model for enhancing initial reading and writing skills, examines its implementation, and analyzes the advantages and disadvantages of its application in MI Islamiyah Reban's learning environment. Employing a qualitative field research approach in education, data collection methods encompass observations, interviews, and documentation to augment the dataset. The analysis relies on descriptive qualitative techniques to elucidate the collected data, with data validation performed through triangulation, cross-referencing multiple sources, and drawing comprehensive conclusions. The study's findings indicate that the Inkaber model, which entails presenting familiar images and matching them with appropriate vocabulary, followed by constructing simple sentences, positively impacts students' reading and writing skills. Evidenced by students' active participation and heightened enthusiasm for reading and writing, this approach enhances their engagement in the learning process. Consequently, students exhibit greater interest in classroom activities due to the utilization of familiar visuals as learning aids.